The Universal Discount as a Means of Economic Stabilization - Baker, J. G. (Econometrica, 1948)
THE TERM universal discount, abbreviated u.d., is used to indicate that a percentage discount (or a percentage bounty if the discount is negative) applies to all payments. Thus, payments for wholesale, retail, and producer goods, payments for capital stock, bonids, debts, dividends, interest, rent, and taxes, payments for wages, salaries, and fees; in short, all transfers of funds where the control of the funds is also transferred are included. Transfers of funds where storage is intended and the control of the funds is not altered, as in the case of bank demand deposits for example, would not be considered payments and would not carry the u.d. It is shown that in a model economic system roughly representative of a free economy the u.d. adjusted according to a simple formula removes instability. There is reason to believe without reference to this particular model that the same u.d. adjustment would be a powerful stabilizing influence under actual conditions. Fortunately, since the adjustment would raise (lower) prices when they are tending upward (downward) there would apparently be no serious policing problem in the enforcement of the u.d. adjustment. Since the u.d. changes prices, wages, rents, interest, fees, taxes, etc. all by the same ratio, there is no direct effect of the u.d. on real income as measured currently. Stating it differently, those with unchanging monetary reserves are not directly affected by the u.d. Consequently the introduction of the u.d. for stabilization purposes would involve significant loss only to those who persist in contributing to instability. Conversely only those contributing to stability would be rewarded. The latter would aid sections of an economy that are hard pressed by business-cycle changes. For example, during a rising price level the shrinkage of real income of those on a fixed money income would be reduced. With the u.d. method, such devices as ordinary price control, control of investment, tax-rate variation during the phases of the business cycle, active monetary policy, government spending, would be unnec-